A Study of Electrical Resistance Tomography on Inhomogeneous System - Ang, Vernoon; Rahiman, M.H.F.; Rahim, R.A.; Talib, M.T.M.; Pusppanathan, Jaysuman; Jamaludin, Juliza (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This study is conducted to investigate inhomogeneous in Electrical Resistance Tomography system using COMSOL Multiphysics finite element software. An inhomogeneous system is represented with the concrete-steel medium. Three type of cases which are varies the dimension of steel, varies a number of steel phantom in concrete, and different location of steel in concrete are the subject in this study. Each case uses results from adjacent and opposite current driven method for comparison. As a result, extension in steel dimension could benefit the ERT system to obtain a good measurement. Also, as a number of steel placed in concrete medium increases, the potential difference will drop when compared with homogenous. It is demonstrated that as a phantom is placed close to the source or measuring electrode area, it could show changes in potential difference reading. In conjunction with that, that area indirectly becomes more sensitive and feedback.